Możliwości zagospodarowania Wyspy Grodzkiej w Szczecinie w aspekcie warunków geotechnicznych międzyodrza = The possibilities of Grodzka Island in Szczecin land development in the aspect of interriver site geotechnical conditions - Borkowski, Marek; Mrozińska, Gabryela; Szutowicz, Julita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents an attractive way of development of Grodzka Island in Szczecin, which was used as a recreation water sport centre in the past. Moreover, based on geological characteristic and analysis of the soil substratum features, an initial assessment of technical difficulties related to foundations of planned objects in the area has been included.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)